Effect of Tides and Storm Surges on Storm Waves at the Northern Coastal Areas of Vietnam - Thuy, Nguyen Ba (VNU Journal of Science: Earth and Environmental Sciences; Vol 35 No 2DO - 10.25073/2588-1094/vnuees.4388, 2019)
Abstract: In this study, the effect of tides and storm surges on storm waves at the Northern coastal area of Vietnam is investigated by a coupled model of surge wave and tide (called: SuWAT). In particular, tide and storm surge are simulated by two-dimensional long wave equations taking into account the wave radiation stress, obtained from the SWAN model. The numerical was then applied to simulate storm waves and surges for typhoon Frankie (7/1996), Washi (7/2005) and Doksuri (9/2017). In the case of the super typhoon, the intensity of typhoon Washi is increased to level 16 (super typhoon level) but remains the same trajectory and operating time. The numerical results showed relatively well with observation data on storm surge and wave height. In general, the wave height is higher in the region  near  the  coast and lower at offshore when considering the effect of tide and storm surge on storm wave. It also indicated that the effect of storm surge on storm wave is more significant than the tide. The results of the study are the basis for proposing to improve the wave forecasting technology in the study area. Keywords: Storm wave, tides, storm surge, super typhoon. References : .Đ. Chiến, N.B. Thủy, N.T. Sáo, T.H. Thái, S. Kim. Nghiên cứu tương tác sóng và nước dâng do bão bằng mô hình số trị, Tạp chí Khí tượng Thủy văn 647 (2014) 19-24. [2] T.Q. Tiến, P.K. Ngọc, Kết nối mô hình SWAN với mô hình WAM thành hệ thống dự báo sóng biển cho vùng Vịnh Bắc Bộ, Tạp chí Khí tượng Thủy văn 651 (2014) 21-26. [3] Y. Funakoshi, S.C. Hagen, P. Bacopoulos. Coupling of hydrodynamic and wave models: case study for Hurricane Floyd (1999) Hindcast, Journal of Waterway, Port, Coastal and Ocean Engineering 134 (2008) 321-335. [4] S.Y. Kim, T. Yasuda, H. Mase, Wave set-up in the storm surge along open coasts during Typhoon Anita, Coastal Engineering 57 (2010) 631-642. [5] X. Bertin, K. Li, A. Roland, J.R. Bidlot. The contribution of short waves in storm surges: two recent examples in the central part of the bay of Biscay, Continental Shelf Research 96 (2015) 1-15. [6] H.Đ. Cường, N.B. Thủy, N.V. Hưởng, D.Đ. Tiến. Đánh giá nguy cơ bão và nước dâng do bão tại ven biển Việt Nam, Tạp chí Khí tượng thủy văn 684 (2018) 29-36. [7] Delf University of Technology. SWAN Cycle III Verion 40.31, User Guide. Delf, 2004. [8] N.B. Thủy, H.Đ. Cường, D.Đ. Tiến, Đ.Đ. Chiến, S. Kim. Đánh giá diễn biến nước biển dâng do bão số 3 năm 2014 và vấn đề dự báo, Tạp chí Khí tượng Thủy văn 647 (2014) 14-18. [9] N.B. Thuy, S. Kim, D.D. Chien, V.H. Dang, H.D. Cuong, C. Wettre and L. R. Hole. Assessment of Storm Surge along the Coast of Central Vietnam, Coastal researcher Journal 33 (2017) 518-530. [10] V.H. Đăng, N.B. Thủy, Đ.Đ. Chiến, S. Kim. Nghiên cứu đánh giá định lượng các thành phần nước dâng trong bão bằng mô hình số trị, Tạp chí Khoa học Công nghệ Biển 17 (2017) 132-138. [11] T. Fujita. Pressure distribution within typhoon, Geophysical Magazine 23 (1952) 437-451.